Structural and metabolic features of the femur of rats after the implantation of glass crystalline material - Shimon, Vasyl; Ashukina, Nataliya; Leontyeva, Frieda; Alfeldi, Sergii; Sheregii, Andrii; Savvova, Oksana; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
In vivo research is an important link in the development of osteoplastic materials. Aim: to study the structural features and markers of bone metabolism after an implantation into the distal metaphysis of the rat femur of glass crystalline calcium phosphate material (GCM). Methods: hole defects in the distal metaphysis of the femur were performed in 28 white laboratory male rats (age 4 months, weight 200–260 g). GCM cylindrical samples with a diameter of 1 mm and a height of 3 mm were placed in defects. A comparison group for biochemical studies was 5 intact rats. Animals were sacrificed 7, 14, 28, and 90 days after surgery. The histological studies of the bone structure around the implant and assessment of osseointegration were performed. In the blood serum the activity of alkaline phosphatase, the content of chondroitin sulfates, urea, the activity of alanine aminotransferase were determined. Results: 7 days after surgery the relative content of bone tissue around implants was (28.59 ± 1.33) %, after 14 days it increased by 2.71 times (p < 0.001). After 30 days bone tissue was located around the entire perimeter of the implant. Bioresorption of the material continued throughout the observation period. A significant increase in the activity of the alkaline phosphatase in blood serum compared with the rate of intact rats was shown from the 7th to the 30th day of observation. The maximum increase of chondroitin sulfates was recorded on the 7th day. The content of urea in the blood serum and the activity of alanine aminotransferase did not statistically significantly differ in terms of the experiment or from indices of intact animals. Conclusions: the studied material is biocompatible, has osteoinductive and osteoconductive qualities. After implanting it into the bone, bone repair is not impaired, and lamellar bone tissue is formed for the final study period (90 days). A characteristic feature of the material is its gradual resorption until the 90th day of observation.